Research progress of oral hairy leukoplakia - MO Longhui, LIANG Jing, WANG Jiongke, LIU Tiannan, ZENG Xin (Kouqiang yixue)
Oral hairy leukoplakia is an oral mucosal disease caused by Epstein-Barr virusinfection of oral squamous epithelial cells. Oral hairy leukoplakia presents as a non-removable, corrugated and wrinkled white plaque sometimes with hair-like projections, typically occurring on the border of the tongue. It is commonly found in patients infected by human immunodeficiency virus, and it can also be seen in immunocompetent and immunocompromised patients who are not infected by human immunodeficiency virus. The pathogenesis of oral hairy leukoplakia is still unclear, and anti-EBV therapy is the main treatment for oral hairy leukoplakia at present. This paper will review the etiology, pathogenesis, risk factors, epidemiology, clinical manifestations, diagnosis and treatment of oral hairy leukoplakia.